Influence of synthesis conditions on the crystallinity of hydroxyapatite obtained by chemical deposition - Toropkov N. E. Nikita Evgenievich; Vereshchagin (Vereschagin, Vereshagin) V. I. Vladimir Ivanovich; Petrovskaya T. S. Tatyana Semyonovna; Antonkin N. S. Nikita Sergeevich (2016, 2016)
Title screen